Effect Of Material Testing Added To Brick Waste Light To Power Support Land In Sukodadi District - Rio Rahmah Dhana; Khafid Afrizal Aulia (Jurnal Scientia, 2024)
Wrong One problem Which Possible faced by para planner And construction implementation, especially for road pavement construction is a way of dealing with poor soil or materials so that they can be used as pavement material. The problem of the level of density and bearing capacity of the soil is wrong one thing that really needs to be considered in planning and work something construction building civil. Matter This because land works as media Which withhold burden or action from construction Which built in on it. Change Weather and temperature in the field are factors that make soil unstable . This research aims to determine the effect of adding lightweight brick waste to clay soil Subdistrict Sukodadi and knowing how to improve mark stability land clay in Subdistrict Sukodadi given addition waste brick light with presentation mix5%, 10%, And 15%. The results of the research carried out can be concluded that for the experiment the addition of local lightweight bricks from the Sukodadi sub-district, Lamongan district, mixed with several variations of 5%, 10%, 15% can increase the carrying capacity of the clay soil of Sukodadi sub-district. Of course, the 10% Light Brick mixture shows very efficient results which can be seen from each CBR test process from the 5% to 15% mixture showing a stable increase.